A comparison of referral pattern and physiotherapy role in two hospitals: the physicians' perception - Ayiesah Ramli (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2005)
The purpose of this study is to compare the doctors' perception of the professional role of physiotherapists, reasons for patient referral to the physiotherapist, the frequent modality referred and suggestions on how to improve the professional role of physiotherapist in two different hospitals, Hospital Universiti Kebangsaan Malaysia (HUKM) and Hospital Kota Kinahalu (HKK). A two-part questionnaire was used to survey the sample of physicians. The first part contained demographic variables whereas the second part contained attitudinal statements based on Moore's criteria of professionalism, reasons for referral, the common treatment modalities that is referred and suggestion on how to improve the professional image of physiotherapist. Three hundred and fifty questionnaires were distributed and two hundred and nine were returned. Out of'this total, 116(66%) subjects were from Hospital Universiti Kebangsaan Malaysia (HUKM) and 93(44%) from Hospital Kota Kinabalu (HKK). The results indicated that the responding doctors viewed the physiotherapists as possessing some degree of professionalism, 52% (65) from HUKM and 68% (63) from HKK, however there was relatively less agreement with the professional aspect of knowledge, skills and autonomy of judgment posed by the physiotherapist. There was a common perception of doctors towards physiotherapy image with more collegial nature among doctors in HKK than those in HUKM. The priority for treatment modalities referred are 66% (77) chest physiotherapy in both hospitals, 54% (61) exercises and mobilizations in HUKM and 45% (53) in HKK, use of 15% (17) electrotherapy agents in HUKM while 22% (26) in HKK and less referral on wax therapy with 3%(3) in HUKM and 8% (7) in HKK and lastly 2% (2) in HUKM and 3% (3) in HKK on hydrotherapy. In both hospitals, 41% (48) of doctors have suggested more discussions happening between physician and physiotherapist in HUKM and 46% (43) in HKK, however 38% (35) doctors from HKK and only 14% (16) from HUKM have encouraged the use of pamphlets as a means of giving more information on the physiotherapy role.